2008
DOI: 10.1007/s00221-008-1411-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual sequence learning in a serial reaction time task

Abstract: In the serial reaction time task (SRTT), a sequence of visuo-spatial cues instructs subjects to perform a sequence of movements which follow a repeating pattern. Though motor responses are known to support implicit sequence learning in this task, the goal of the present experiments is to determine whether observation of the sequence of cues alone can also yield evidence of implicit sequence learning. This question has been difficult to answer because in previous research, performance improvements which appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
73
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 29 publications
6
73
0
Order By: Relevance
“…In fact, given that this advantage was present from the beginning of the task procedural learning could have been gained through the previous observational training. This is in accordance with a recent study demonstrating that observation supports implicit sequence learning even in the absence of any explicit knowledge (Song, Howard, & Howard, 2008). Nevertheless, the different performances shown after observational learning and practice-based learning might also have been due to differences in the mechanism responsible for supporting skill acquisition.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, given that this advantage was present from the beginning of the task procedural learning could have been gained through the previous observational training. This is in accordance with a recent study demonstrating that observation supports implicit sequence learning even in the absence of any explicit knowledge (Song, Howard, & Howard, 2008). Nevertheless, the different performances shown after observational learning and practice-based learning might also have been due to differences in the mechanism responsible for supporting skill acquisition.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we think that the reduction in the total process time to final motor response may be attributed to the rapid onsets of muscle activation and movement initiation as motor sequential learning progressed. Our findings, showing a decline in total processing times, were in line with previous learning experiments with the SRT task, which exhibit a gradual reduction of the reaction time 5,11,12,15,16) . It has previously been established that motor sequential learning is accomplished by acquisition of explicit and implicit knowledge in multiple brain areas, including the cortical and subcortical structures 2,[17][18][19] .…”
Section: Discussionsupporting
confidence: 92%
“…Many previous studies have shown that motor sequential learning leads to a reduction in the reaction time and an improvement in correct responses, accompanied by efficient and effective processing in the neuromuscular system 5,11,12) . A c c o r d i n g t o f u n c t i o n a l M R I a n d electroencephalography, cortical excitability and the involved regional area are altered after motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…Recent behavioral evidence has shown that learning on the SRT task can proceed when responses are confined to sequential covert reorienting of visuospatial attention (Song et al, 2008). Hence, motor responses are not a necessary condition for complex sequence learning.…”
Section: Introductionmentioning
confidence: 99%